2015
DOI: 10.3892/or.2015.4521
|View full text |Cite
|
Sign up to set email alerts
|

CD24 promotes the proliferation and inhibits the apoptosis of cervical cancer cells in vitro

Abstract: The protein CD24 is a cell surface protein that appears to function as an adhesion molecule; its expression has been shown to correlate with prognosis in a variety of tumors. Herein, we investigated the possible role and mechanism of CD24 in cervical cancer. Our results showed that CD24 was overexpressed in cervical cancer tissues compared with that in the adjacent non‑cancerous tissues by qPCR, immunohistochemistry and western blotting technologies. To explore the possible mechanism of CD24 in cervical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…CD24 is overexpressed in various human malignancies (cervical, gliomas, breast, pancreas, esophageal squamous cell carcinoma, gastric, bladder, and colorectal). In in-vivo and in-vitro cancer models, it was suggested that CD24 promotes colorectal, cervical, and breast cancer cell proliferation [4][5][6][7]. CD24 is also considered a marker for cancer [8] and thus was proposed as a diagnostic tool for cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…CD24 is overexpressed in various human malignancies (cervical, gliomas, breast, pancreas, esophageal squamous cell carcinoma, gastric, bladder, and colorectal). In in-vivo and in-vitro cancer models, it was suggested that CD24 promotes colorectal, cervical, and breast cancer cell proliferation [4][5][6][7]. CD24 is also considered a marker for cancer [8] and thus was proposed as a diagnostic tool for cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous proteins, including cluster of differentiation (CD)44, CD24, CD38, Fos-related antigen-1, heat shock protein β-1 and transcription factor SOX-9, have been implicated in cervical cancer, and dysregulation of these proteins is closely associated with the occurrence and outcome of cervical cancer (34)(35)(36)(37)(38)(39). However, the etiology of cervical carcinoma remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…CD24, an adhesive molecule and one of molecular biomarkers of cancer stem cells, is associated with cancer cell proliferation and migration [ 34 , 35 ], and cells with CD24 expression may be the cancer-initiating cells that promote tumor migration and metastasis [ 36 38 ]. Wang and his colleagues reported that CD24 expression increased gradually in samples of normal gastric mucosa, non-atrophic chronic gastritis, chronic atrophic gastritis (CAG), CAG with intestinal metaplasia, dysplasia and GC [ 19 ].…”
Section: Discussionmentioning
confidence: 99%